Proceedings of the 57th Annual Meeting of the Association for Computational Linguistics 2019
DOI: 10.18653/v1/p19-1623
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Word Omission Errors in Neural Machine Translation: A Contrastive Learning Approach

Abstract: While neural machine translation (NMT) has achieved remarkable success, NMT systems are prone to make word omission errors. In this work, we propose a contrastive learning approach to reducing word omission errors in NMT. The basic idea is to enable the NMT model to assign a higher probability to a ground-truth translation and a lower probability to an erroneous translation, which is automatically constructed from the ground-truth translation by omitting words. We design different types of negative examples de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Recent work showed that contrastive learning can boost the performance of self-supervised and semi-supervised learning in computer vision tasks (He et al, 2020;Chen et al, 2020a;Khosla et al, 2020). In natural language processing, contrastive learning has been investigated for several tasks, including language modeling (Huang et al, 2018), unsupervised word alignment (Liu and Sun, 2015) and machine translation (Yang et al, 2019;Lee et al, 2020). In this work, we are interested in applying contrastive learning to chest X-ray report generation in a multi-modality setting.…”
Section: Contrastivementioning
confidence: 99%
“…Recent work showed that contrastive learning can boost the performance of self-supervised and semi-supervised learning in computer vision tasks (He et al, 2020;Chen et al, 2020a;Khosla et al, 2020). In natural language processing, contrastive learning has been investigated for several tasks, including language modeling (Huang et al, 2018), unsupervised word alignment (Liu and Sun, 2015) and machine translation (Yang et al, 2019;Lee et al, 2020). In this work, we are interested in applying contrastive learning to chest X-ray report generation in a multi-modality setting.…”
Section: Contrastivementioning
confidence: 99%
“…Compared to the above methods, our approach does not need to generate extra positive samples. Although (Yang et al, 2019) propose a sentence-level margin loss-based method for machine translation to reduce the word omission errors and do not need positive samples too, their negative samples are generated by word omission at the token level and cannot be used in GEC. In contrast, our approach uses beam search to generate erroneous sentences as negative samples at the sentence level, which effectively prevents the model from making mistakes and thus is more suitable for the GEC task.…”
Section: Contrastive Learningmentioning
confidence: 99%
“…How to construct examples is an important issue in contrastive learning. For the translation task, Yang changed the number of omitted words, word frequency, and part of speech according to the actual translation, designed different types of negative examples to realize data augmentation [29]. Wu and Meng proposed to use word deletion, reordering, and substitution to achieve it [30,31].…”
Section: Introductionmentioning
confidence: 99%